Corneal incision enlargement in two preloaded intraocular lens injectors: an intraindividual in vivo study - Yildirim, Timur Mert; Łabuz, Grzegorz; Baur, Isabella; Poompokawat, Piyanut; Knorz, Michael C.; Auffarth, Gerd U.; Khoramnia, Ramin (Journal of refractive surgery, 2021)
PURPOSE:To assess enlargement of the clear corneal incision site and functional outcome in patients with cataract, following the use of two preloaded intraocular lens (IOL) injectors.METHODS:In this prospective, randomized, intraindividual comparative clinical study, 58 paired-eyes were randomly assigned for implantation with two preloaded injectors: AutonoMe with a Clareon IOL (Alcon Laboratories, Inc) and iSert with a Vivinex IOL (Hoya). The size of the corneal incision, 2 mm for the iSert and 2.2 mm for the AutonoMe, was measured before and after phacoemulsification and after IOL implantation. Patients were examined 3 months after surgery to assess keratometry, subjective refraction, and visual acuity.RESULTS:The incision enlargement was 0.20 ± 0.10 mm for the AutonoMe and 0.29 ± 0.10 mm for the iSert, with a statistically significant difference (P < .05). The final wound size after IOL implantation was 2.41 mm for the AutonoMe and 2.35 mm for the iSert. The mean absolute surgically induced astigmatism (SIA) was 0.50 ± 0.25 diopters (D) in the iSert eyes and 0.45 ± 0.20 D in the AutonoMe eyes (P > .05). The 3-month postoperative uncorrected and corrected distance visual acuity (UDVA and CDVA) were similar in both groups, with a UDVA of 0.10 and 0.12 logMAR and CDVA of −0.04 and −0.03 logMAR, respectively for the AutonoMe and iSert.CONCLUSIONS:The iSert injector caused more enlargement of the corneal wound during IOL implantation compared to the AutonoMe. Despite the initially different incision sizes, the final incision size and functional outcomes were similar in both groups.[J Refract Surg. 2021;37(5):331-336.]